Management of Integrated Education between Pesantren and Campus in Improving The Quality of Graduates (Multisites Study in Ma'had Dalwa Bangil and Pondok Ngalah Purwosari Pasuruan East-Java) - Muhdi, Ahmad Adip (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2018)
Pesantren or as usually assosiated to an Islamic boarding school is one kind of typical Indonesian Islamic education established by the community. In the process, most of the islamic boarding school seeks to respond to the demands of the times by modernizing its institution by establishing formal educational institutions ranging from pre-schools to higher education level. Besides, several islamic boarding schools try to remain its original characteristics as islamic educational institutions that focuses on tafaqquh fi al-din (religion deepening), which teaches the students how to understand the content of yellow book. Islamic boarding schools that seeks to combine the two dimension, while maintaining its identity as an educational institution that tafaqquh fi al-din but on the other hand also adopted the formal education system, especially higher education is then popularly known as integrated boarding school. This study was interesting to get further investigation in order to analyze and find the concepts and models of management of integrated educational between islamic boarding school and college and the implications for improving the quality of its graduates. This study used a qualitative approach with multisite study as its research design. Finally, the study concluded that the concept of integrated education initiated by Ma'had Dalwa Bangil and Pondok Ngalah Purwosari consist of two different concepts, namely